Dental procedures during fasting: perceptions among Muslims in Malaysia - Mohd, Farah Natashah; Said, Abdul Hadi (Ectodermal Dysplasia Group-Turkey, 2019)
This study aims to assess the perceptions among Muslims in Malaysia on common dental procedures during fasting. A structured questionnaire was used to assess the perception about common dental procedures during fasting on 377 Muslim adults in Kuantan, Malaysia. The total cumulative score derived from the perception section was categorized into good and poor perception based on the median score, where a score less than median score was categorized as poor perception and a score equal to or more than median score was categorized as good perception. We further examined association between perception score with sociodemographic data. Majority respondents perceived that most of the dental procedures will not nullify their fast with 50.9% of them categorized as having good perception based on median score. There was significant association between perception with education level (p=0.04) and Islamic education level (p<0.001). Majority of the Muslims perceived that most dental procedures did not nullify their fast. Hence, further research is necessary to explore the reason for reduced dental attendance among Muslim patients during fasting month despite their good perception.